Prevalence of depression in patients with dementia in a tertiary government Hospital and a teaching hospital in Klang Valley / Layuza Aliasad - Layuza, Aliasad (2013)
Introduction: Dementia is the most common illness that is associated with the geriatric age group. Depression occurs frequently in patients with dementia and has been well demonstrated to increased morbidity and mortality. However, there are limited data available in Malaysia pertaining to depression in patients with dementia. Objective: The main objective of this study is to determine the prevalence of depression in patients with dementia using GDS-15 and M.I.N.I and to examine the associated socio-demographic and clinical factors associated with depression among patients with dementia. Method: This is a cross sectional study on patients who have been diagnosed with dementia attending either psychogeriatric or memory clinic in HKL or memory clinic in UMMC. Their socio-demographic and clinical data were obtained by interviewing patients and care givers and also from the patientsï¿½ records. The GDS-15 and M.I.N.I were used to determine the depression among subjects. Ethical approval to conduct this study was obtained from the UMMC ethics committee and from NIH through NMRR. Results: A total of 114 patients were recruited in the study. Prevalence of major depressive disorder based on GDS-15 score was 20.2% and prevalence of depression vi using M.I.N.I was 10.5%. Depression based on GDS-15 was significantly associated with severity of dementia with adjusted odds ratio of 6 (p=0.006, CI=1.661-20.747). The MMSE score is negatively correlated with GDS-15 (r= -0.335, p<0.01). Conclusion: There was a high prevalence of depression in patients with dementia and it was significantly associated with the severity of dementia. Therefore, dementia patients should be regularly screened for depression during their clinic visit.